2017
DOI: 10.1111/1748-8583.12152
|View full text |Cite
|
Sign up to set email alerts
|

Union membership and job satisfaction: Initial evidence from French linked employer–employee data

Abstract: A number of contradictory theoretical hypotheses have been advanced about the relationship between unionisation and job satisfaction. In this article, new evidence of the effects of unionisation on job satisfaction is presented using French linked employer–employee data from the 2011 REPONSE Survey. A bivariate probit model is estimated to deal with the reverse causation issue that many previous studies have failed to account for. The results indicate that union members are less satisfied with their jobs than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 48 publications
0
26
0
4
Order By: Relevance
“…This idea has been challenged by those who argue that union worker job dissatisfaction reflects poorer working conditions for union workers (Bender and Sloane 1998;Gordon and Denisi 1995;Pfeffer and Davis-Blake 1990). It has also been suggested that those predisposed to job dissatisfaction because of personality and values might be more likely to become union members (Bryson et al 2010(Bryson et al , 2004Clark 1996;Green and Heywood 2015;Heywood et al 2002;Laroche 2017).…”
Section: Theory and Past Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea has been challenged by those who argue that union worker job dissatisfaction reflects poorer working conditions for union workers (Bender and Sloane 1998;Gordon and Denisi 1995;Pfeffer and Davis-Blake 1990). It has also been suggested that those predisposed to job dissatisfaction because of personality and values might be more likely to become union members (Bryson et al 2010(Bryson et al , 2004Clark 1996;Green and Heywood 2015;Heywood et al 2002;Laroche 2017).…”
Section: Theory and Past Researchmentioning
confidence: 99%
“…It is a well-established empirical regularity that union members are less satisfied with their jobs than their non-union counterparts (Borjas 1979;Bryson et al 2010;Freeman 1978;Green and Heywood 2015;Laroche 2017Laroche , 2016. This is widely described as an apparently puzzling or anomalous finding because it is not clear why a worker would join a union if it reduces her job satisfaction (Bryson et al 2010;Freeman 1978;Freeman and Medoff 1984;Green and Heywood 2015;Powdthavee 2011).…”
mentioning
confidence: 99%
“…Outro ponto é a limitação dos sindicatos em infl uenciar a satisfação individual dos trabalhadores (Kalleberg, 1977). Entre os trabalhos que confi rmam essa constatação estão Freeman (1978), Borjas (1979), Clark (2001), Green & Heywood (2008), Garcia-Serrano (2009), Seago et al (2011), Green & Heywood (2015) e Laroche (2017). Para Holland et al (2011), a sindicalização não possui efeito signifi cativo sobre a satisfação laboral, porém, os trabalhadores com voz ativa no trabalho têm, em média, maior satisfação com o trabalho.…”
Section: I1 Satisfação Laboral E Fatores Determinantesunclassified
“…Para Holland et al (2011), a sindicalização não possui efeito signifi cativo sobre a satisfação laboral, porém, os trabalhadores com voz ativa no trabalho têm, em média, maior satisfação com o trabalho. Laroche (2017), na estimação de um modelo probit bivariado para a França, observou uma relação negativa entre os membros dos sindicatos e a satisfação ao considerar as características individuais, do ambiente e do trabalho, especialmente aquelas relacionadas à remuneração. Em um segundo momento, ao aplicar um controle sobre a endogeneidade da fi liação sindical, a diferença na satisfação no trabalho entre trabalhadores sindicalizados e não sindicalizados desapareceu devido ao efeito de seleção em locais de trabalho cobertos apenas por acordos coletivos.…”
Section: I1 Satisfação Laboral E Fatores Determinantesunclassified
“…It is primarily these workers who are dissatisfied who become unionized, and additionally complainers who join unions. Thus, some kind of sorting mechanism explains the differences in job satisfaction between union members and nonmembers (Bender and Sloane, 1998;Hammer and Avgar, 2005;Laroche, 2017). Holland et al (2011) show that the possibility of voice explains the negative effect of union membership in Australia.…”
Section: Introductionmentioning
confidence: 98%